STRATEGI PEMASASARAN PRODUK GULA AREN DI DESA MEKARSARI KECAMATAN GUNUNGSARI KABUPATEN LOMBOK BARAT - I GUSTI MADE SUBRATA (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to find out various alternative marketing strategies for palm sugar products in Mekarsari Village, Gunungsari District, West Lombok Regency. The type of research used is descriptive research with data collection method is case study method and data analysis using SWOT analysis. The results of this study are 1) Promote products by utilizing existing technology, for example through social media. 2) Establish cooperative relationships with various parties, especially those related to the marketing of palm sugar products. 3) Cooperating with food manufacturers that use palm sugar as the basic ingredient